Evaluating the Contribution of Sukuk to Sustainable Infrastructure Financing in Indonesia - Ambarwati, Wulan Sulistya (Islamicate Institute, 2025)
Infrastructure development plays a vital role in a country’s overall progress and competitiveness. According to the 2019 Global Competitiveness Report, Indonesia ranks 50th out of 141 countries, with infrastructure remaining one of its weakest indicators. This highlights the urgent need to accelerate infrastructure improvements. However, such development requires substantial financial resources that exceed the capacity of the state budget. To address this challenge, the Indonesian government has adopted sukuk (State Sharia Securities) as an alternative financing instrument. Since their initial issuance in 2008 through January 2020, sukuk issuances have reached IDR 1,230.44 trillion, with an outstanding value of IDR 738.37 trillion, financing 2,939 infrastructure projects across 34 provinces. These achievements demonstrate the significant and growing role of sukuk as a strategic instrument in supporting sustainable infrastructure development in Indonesia.